S. Giovanni Varieties (Pyrus communis L.): Antioxidant Properties and Phytochemical Characteristics. (2nd June 2019) - Azzini, Elena; Maiani, Giuseppe; Durazzo, Alessandra; Foddai, Maria Stella; Intorre, Federica; Venneria, Eugenia; Forte, Valentina; Lucchetti, Sabrina; Ambra, Roberto; Pastore, Gianni; Silveri, Donato Domenico; Maiani, Gianluca; et al.
Abstract : In order to evaluate and identify the antioxidant properties and the phytochemical characteristics, as well as the role of the genetic background and the different fruit parts in the definition of fruit quality, we characterized the existing germplasm through nuclear simple sequence repeats (SSRs) and evaluated the genetic divergence between ancient S. Giovanni varieties ( Pyrus communis L.) and different types of grafting in relation to some variables of fruit quality. On the peel and pulp of pear varieties, the contents of flavanols, flavonols, and hydroxycinnamic acids as well as total antioxidant capacity were assessed. Their role in plant defences was confirmed by a significantly higher amount in the peel (206.66 ± 44.27, 48.45 ± 13.65, and31.11 ± 11.94   mg / 100   g, respectively) of S. Giovanni pears than in the pulp (71.45 ± 34.94, 1.62 ± 0.83, and17.05 ± 5.04   mg / 100   g, respectively). Data obtained using capillary analysis of SSR indicate unequivocally that the four samples of San Giovanni varieties can be divided into 3 different genetic groups. Cultivar and the different parts of the fruit can exert an action in the definition of the quality product. The use of local varieties and ecotypes can be considered a valid tool to improve food quality and at the same time to support local agrobiodiversity.